Solid pseudopapillary neoplasms of the pancreas: Case series with a review of the literature - Uğuz, Alper; Ünalp, Ömer Vedat; Akpınar, Göksever; Karaca, Can Avni; Oruç, Nevin; Nart, Deniz; Yılmaz, Funda; Aydın, Ahmet; Çoker, Ahmet (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The solid pseudopapillary neoplasms are quite rare tumors of the pancreas, comprising roughly 1-2% of all pancreatic neoplasms. It has a low malignant potential and usually affects young females. Despite increasing number of articles in the last decade, there is still debate on the pathogenesis, malignant potential and optimal surgical strategy for the solid pseudopapillary neoplasms. Materials and Methods : Medical recordings of 326 patients who were operated due to pancreatic mass were retrospectively analyzed. Patient demographics, presenting symptoms, surgical and pathologic characteristics of the tumor, postsurgical course, long-term survival, and other relevant data were extracted from patients’ charts. Results: Majority of the patients were female in consistency with the classic data in the literature. All the patients underwent curative intent resections. Tumors were commonly localized in the tail of the pancreas making distal pancreatectomy the most commonly performed surgical procedure. Mean tumor diameter was 5.8 centimeters with tumor sizes ranging from 1 to 19 cm. Conclusion: The solid pseudopapillary neoplasms of the pancreas is a rare tumor with low malignant potential, which is more common in females of reproductive age, with abdominal pain being their most common presentation. The short-term outcomes in patients following surgical R0 resection are excellent. However, proximal placement of the tumor and female gender may have slightly worse prognosis. We hope that our findings from a series of patients represent a contribution to the existing literature on SPN, and authors declare their willingness to provide further details for future meta-analyses.